2019
DOI: 10.1007/s11031-019-09766-w
|View full text |Cite
|
Sign up to set email alerts
|

The internalization of and defiance against rules within prison: The role of correctional officers’ autonomy-supportive and controlling communication style as perceived by prisoners

Abstract: While incarcerated, prisoners are subject to a vast number of rules. Drawing upon Self-Determination Theory, the present study examined whether prisoners' perceptions of the degree to which prison officers communicate rules in an autonomy-supportive or controlling way related to prisoners' internalization of and defiance against rules, and whether this, in turn, related to their (mal)adaptive functioning in prison. Participants were 156 Belgian prisoners (Mage = 38.60; SD = 11.68, 88.5% male) who filled out qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
(70 reference statements)
0
11
0
Order By: Relevance
“…Introjection is also a controlled form of internalization because even though the contingency driving behavior is "within" the person, the PLOC is still phenomenally external; there is an experience of pressure on the self to act or face the affective and self-evaluative consequences. Introjection has been studied in many life domains, such as putting effort into schoolwork (van der Kaap-Deeder et al, 2016), sport (Pelletier et al, 2001), adhering to religious beliefs (Ryan et al, 1993), or achieving a thin "ideal" (Verstuyf et al, 2016). Introjection has also been developmentally linked with parental control and conditional regard, in which relatedness is expressed contingently on meeting parental standards (e.g., Kanat-Maymon et al, 2016).…”
Section: Extrinsic Motivations and Their Relative Autonomymentioning
confidence: 99%
See 1 more Smart Citation
“…Introjection is also a controlled form of internalization because even though the contingency driving behavior is "within" the person, the PLOC is still phenomenally external; there is an experience of pressure on the self to act or face the affective and self-evaluative consequences. Introjection has been studied in many life domains, such as putting effort into schoolwork (van der Kaap-Deeder et al, 2016), sport (Pelletier et al, 2001), adhering to religious beliefs (Ryan et al, 1993), or achieving a thin "ideal" (Verstuyf et al, 2016). Introjection has also been developmentally linked with parental control and conditional regard, in which relatedness is expressed contingently on meeting parental standards (e.g., Kanat-Maymon et al, 2016).…”
Section: Extrinsic Motivations and Their Relative Autonomymentioning
confidence: 99%
“…In the work domain, a meta-analysis by Slemp et al (2018) found that leader autonomy support showed increasingly positive associations with more internalized forms of motivation, effects that were mediated by basic need satisfactions and not moderated by country. Even in the generally restrictive context of prisons, internalization of rules can be fostered through more autonomy-supportive guards and staff (van der Kaap-Deeder et al, 2019). An important theme across this literature is that for individuals to take responsibility for activities, they need to experience supports for not just efficacy but also autonomy (Hornstra et al, 2020).…”
Section: Support For Basic Psychological Needs In Internalization And...mentioning
confidence: 99%
“…Although children generally became less aggressive with age, mothers whose parenting practices were more controlling had children whose trajectory of aggression remained highest, even when controlling for other risk factors. Van der Kaap-Deeder and colleagues (2019) studied Belgian prisoners and found positive associations between the controlling style of correctional officers and inmate-reported aggression. Taken together, such varied studies suggest that the degree to which people experience autonomy or control may play a role in the prosocial and antisocial outcomes, across domains.…”
Section: Autonomy Control and Internalizationmentioning
confidence: 99%
“…In addition, both frameworks converge in their claims that the quality of communication is of critical importance for understanding whether and when people will internalize and endorse the value of rules and regulations, and whether they will act upon them voluntarily (Ryan & Deci, 2017). In line with this, autonomy-supportive strategies have been shown to promote the internalization of rules and norms across different contexts, including the family context (e.g., internalization of parental prohibitions; Van Petegem, Vansteenkiste, et al, 2017a) and the legal context (e.g., internalization of prison rules; Van der Kaap-Deeder et al, 2019), thereby using longitudinal (Vansteenkiste et al, 2014), observational (e.g., Laurin & Joussemet, 2017), and vignette-based designs (e.g., .…”
Section: Internalization Within Sdtmentioning
confidence: 91%
“…Such histories may lead to the internalization of a completely different set of values that undermine the law rather than bolster it (Moule et al, 2019). However, past SDT-based research suggests that autonomy support (which is akin to procedural justice) is linked to greater internalization in samples of adolescents with severe emotional and behavioral problems (Savard et al, 2013) and among prisoners (Van der Kaap-Deeder et al, 2019).…”
Section: Limitations and Avenues For Future Researchmentioning
confidence: 99%